2005
DOI: 10.1002/mame.200400177
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behaviour of Fibre‐Reinforced Syntactic Foams

Abstract: Summary: Syntactic foams containing 0.9, 1.76, 2.54, 3.54 and 4.5 vol.‐% of E‐glass fibres in the form of chopped strands were processed and subjected to three‐point bending tests. The results showed that introduction of chopped strand fibres into the syntactic foam system increased the flexural strength. The values increased with the amount of fibres in the foam system except for the one containing 3.5 vol.‐% of fibres, which showed a lower value than other fibre‐reinforced systems, thereby deviating from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…Studies on three-point bend tests have been conducted in either flexural [14,23] or short beam shear test configurations [15][16][17]. In addition, fiber reinforced syntactic foams [24][25][26] and syntactic foam core sandwich composites have also been studied for bending properties [27]. Several studies on fracture toughness of syntactic foams have tested pre-cracked specimens under three-point bend conditions [28][29][30][31].…”
Section: Introductionmentioning
confidence: 98%
“…Studies on three-point bend tests have been conducted in either flexural [14,23] or short beam shear test configurations [15][16][17]. In addition, fiber reinforced syntactic foams [24][25][26] and syntactic foam core sandwich composites have also been studied for bending properties [27]. Several studies on fracture toughness of syntactic foams have tested pre-cracked specimens under three-point bend conditions [28][29][30][31].…”
Section: Introductionmentioning
confidence: 98%
“…Presently, embedding short fibres in syntactic foams is a viable means for enhancing the flexural properties of syntactic foams. Many researchers reported that the incorporation of chopped strand glass fibres or carbon fibres could improve the flexural properties of syntactic foams [1,[7][8][9]. However, this method has some limitations; short fibres are hard to uniform disperse and may cluster and bunch in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the clustering and bunching, the fibres are not completely wet by the matrix hence the fibres are less effective in bearing the load. And even worse, the incomplete wet fibres can make the interface region to be filled with air and eventually reduce the mechanical properties of the whole materials [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, due to this clustering, the fibers were not completely wet by the resin matrix; hence the fibers were less effective in bearing the load transferred from the matrix. Thus, the latter method was found to be more effective, as evident from the lower void content and good mechanical properties [123,124]. The compressive modulus also increased with the content of fibers in the system, except for the one containing 3.54% of fibers, which showed a lower value than other fiber-reinforced systems [125].…”
Section: Fiber-reinforced Syntactic Foamsmentioning
confidence: 75%